THE ROLE OF URBAN MORPHOLOGY AND CULTURAL MEMORY IN SHAPING CITY IDENTITY - Kosmii, Mykhailo; Grebeniuk, Ivan (Theory and practice of design, 2025)
The article examines the interrelation between the urban spatial morphology and cultural memory as key factors in the process of shaping the socio-cultural identity of a city. The purpose of the study is to identify the role of morphological structure of the urban environment and symbolic carriers of memory in constructing the identity of contemporary Ukrainian cities. Methodology is based on an interdisciplinary approach that combines methods of architectural and urban planning analysis, cultural interpretation, historical-genetic and comparative analysis, as well as the concepts of “lieux de mémoire” (P. Nora) and cultural memory theory (J. Assmann). The results are substantiated through the typologization of material and intangible factors of urban space, and by analyzing specific cases of Ukrainian cities (Kyiv, Lviv, Ivano-Frankivsk, Odesa, Kharkiv). Results demonstrate that the spatial and morphological framework of the city provides the foundation for preserving historical and architectural heritage, while cultural memory assigns symbolic meanings to this space. Different models of identity formation were identified: Kyiv, Lviv, and Kharkiv rely primarily on material heritage; Odesa emphasizes intangible cultural codes; Ivano-Frankivsk represents a balanced combination of both dimensions. Scientific novelty lies in the development of a conceptual model of interaction between urban morphology and cultural memory in shaping the socio-cultural identity of the city, as well as in the proposed typology of material and intangible factors that influence the identification of urban space. Practical relevance of the results is determined by their applicability in urban development strategies, particularly in heritage preservation, public space design, and territorial branding. The findings can be used by architects, urban planners, cultural theorists, and spatial planning specialists to improve the quality of urban environments and their alignment with the identity needs of local communities.